CIRCASSIAN QUESTION IN THE CURRENT ACTIVITIES OF KABARDIAN PUBLIC ASSOCIATIONS - A. V. KUSHKHABIEV (Кавказология, 2021)
It was revealed that at the beginning of the XXI century joint activities of some Kabardian public associations, founded at the beginning of the XXI century (Circassian Congress, etc.), and some other Circassian public associations of the Russian Federation and the Circassian diaspora was focused on solving the components of the Circassian question at the federal and international levels: the problem of recognizing and condemning the Circassian genocide committed by tsarism at the end of the 18th–19th centuries, the problem of repatriation and emergency evacuation of Circassians from Syria to Russia. The International Circassian Association carried out activities to solve at the federal level the problem of granting to foreign Circassians, in particular Syrian, obtaining Russian citizenship in a simplified manner in accordance with the legislation of the Russian Federation on foreign compatriots. But Circassian public associations and ICA failed to achieve a solution to these problems at the federal level. The joint activities of Kabardian and other Circassian public associations of the Russian Federation and the Circassian diaspora on the solution of the Circassian question at the beginning of the XXI century, as well as the divergence of their positions on the question of holding the XXII Olympic Winter Games in Sochi (boycott by one group and support by another), testify about the preservation in the historical memory of the Adyghe people and, especially, in the memory of foreign Circassians of the large-scale tragedy in the New history of the Caucasus – the mass eviction of the Circassians into the Ottoman Empire, carried out by the authorities of Tsarist Russia (1858–1865), about the urgency of the problem of repatriation foreign Circassians.